2023
DOI: 10.1021/jacs.3c09566
|View full text |Cite
|
Sign up to set email alerts
|

Highly Birefringent d0 Transition Metal Fluoroantimonite in the Mid Infrared Band: Order–Disorder Regulation by Cationic Size

Jia-Hang Wu,
Chun-Li Hu,
Ting-Kun Jiang
et al.

Abstract: An unusual O/F ordered d 0 transition metal fluoroantimonite, namely, K 2 SbMoO 2 F 7 , has been created by the cationic size effect of alkali metals. It features the largest birefringence of 0.220@550 nm among inorganic antimonites with a halogen element, which is an order of magnitude larger than the disordered A 2 SbMoO 2 F 7 (A = Rb, Cs). These three new compounds exhibit two different structures, although all of the structures were made of [SbMoO 2 F 7 ] 2− chains formed by SbF 5 square pyramids and MoO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Exploring new material systems is of great importance, because it contributes to expand the chemical space and discovery novel materials with unique properties and potential applications. By investigating new inorganic compound systems, researchers can uncover unprecedented structural motifs, understand the relationships between structures and properties, and potentially develop advanced materials for various technological applications. Selenites have garnered the attention of scientists due to their unique physical and chemical properties. They possess stereochemically active lone-electron pairs, making them promising candidates of nonlinear optical (NLO) and birefringent materials . Over the past few decades, research on selenite compounds has identified over a thousand different chemical entities.…”
mentioning
confidence: 99%
“…Exploring new material systems is of great importance, because it contributes to expand the chemical space and discovery novel materials with unique properties and potential applications. By investigating new inorganic compound systems, researchers can uncover unprecedented structural motifs, understand the relationships between structures and properties, and potentially develop advanced materials for various technological applications. Selenites have garnered the attention of scientists due to their unique physical and chemical properties. They possess stereochemically active lone-electron pairs, making them promising candidates of nonlinear optical (NLO) and birefringent materials . Over the past few decades, research on selenite compounds has identified over a thousand different chemical entities.…”
mentioning
confidence: 99%
“…The first is the large anisotropy of the TeO 3 triangular pyramids and the linear O–Hg–Hg–O groups. It is reported that the lone pair electrons of tellurite groups point to the minimum refractive index direction and the maximum refractive index direction is perpendicular to the lone pair electrons. , For the linear groups, the maximum refractive index direction parallels the line. These two groups can display strong anisotropy in the refractive indices.…”
Section: Resultsmentioning
confidence: 99%
“…The anionic groups containing d 0 transition metals with second-order Jahn–Teller (SOJT) distortions are one of the most commonly used NLO-active groups in visible light region, as the out-of-center distortions (e.g., NbO 6 in LN and TiO 6 in KTP) arising from metal dπ–oxygen pπ orbital interactions have the potential to induce noncentrosymmetric (NCS) structures and generate strong SHG intensities. The SOJT distortion also leads to increased polarization anisotropy, making birefringence capable of better PM ability . Extensive attempts including Nb 2 O 3 (IO 3 ) 2 (SO 4 ) (6 × KDP, Δ n = 0.22), LiZrTeO 6 (2.5 × KDP, Δ n = 0.06), BaTeMo 2 O 9 (15 × KDP), BaTeW 2 O 9 (12.5 × KDP), K­(VO) 2 O 2 (IO 3 ) 3 (20 × KDP), BaNbO­(IO 3 ) 5 (14 × KDP), and Cs 3 Nb 5 GeO 16 (Δ n = 0.19) demonstrate success in the visible to IR light regions.…”
Section: Structure Descriptions and Nlo-related Propertiesmentioning
confidence: 99%
“…41−44 The SOJT distortion also leads to increased polarization anisotropy, making birefringence capable of better PM ability. 45 × KDP, Δn = 0.22), 46 LiZrTeO 6 (2.5 × KDP, Δn = 0.06), 47 BaTeMo 2 O 9 (15 × KDP), 48 BaTeW 2 O 9 (12.5 × KDP), K(VO) 2 O 2 (IO 3 ) 3 (20 × KDP), 49 BaNbO(IO 3 ) 5 (14 × KDP), 50 and Cs 3 Nb 5 GeO 16 (Δn = 0.19) 51 demonstrate success in the visible to IR light regions. However, the high distortion usually corresponds to limited band gaps, which seriously influences transparency in short wavelength regions.…”
mentioning
confidence: 99%